KREATIVITAS PENGRAJIN TENUN SONGKET DALAM MENINGKATKAN NILAI EKONOMI PRODUK DI DESA SUMBER HARAPAN KABUPATEN SAMBAS - Hamdai, Hamdai; Matsum, Junaidi H.; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was conducted in Sumber Harapan Village, Sambas District, Sambas Regency. The purpose of this research is to find out the creativity of songket weaving craftsmen and the economic value of the products produced in Sumber Harapan Village, Sambas District, Sambas Regency. The approach used is in the form of qualitative research in the form of case studies. Results of interviews and observations with the number of informants 3 managers and 7 songket weaving craftsmen. Data collection was carried out using in-depth interviews and observation as well as documents relevant to the research. The results of the study show that the creativity carried out by songket weaving craftsmen greatly influences the economic value of the woven products themselves. With the creativity carried out by songket weaving craftsmen, they can create new products and create new innovations so that their development can keep up with the times.